2018
DOI: 10.1155/2018/9621640
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Clinical Decision Support System for Fracture Prediction Using Imbalanced Dataset

Abstract: More than 1 billion people suffer from chronic respiratory diseases worldwide, accounting for more than 4 million deaths annually. Inhaled corticosteroid is a popular medication for treating chronic respiratory diseases. Its side effects include decreased bone mineral density and osteoporosis. The aims of this study are to investigate the association of inhaled corticosteroids and fracture and to design a clinical support system for fracture prediction. The data of patients aged 20 years and older, who had vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 79 publications
0
17
0
Order By: Relevance
“…Among the 32 studies that investigated fracture detection (Table 3), (66–97 ) 11 were on vertebral fractures, ( 66–76 ) 17 hip fractures, ( 74–90 ) and 10 other fracture sites such as humerus or wrist. ( 75,76,90–97 ) Nineteen studies developed CNN models for image analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the 32 studies that investigated fracture detection (Table 3), (66–97 ) 11 were on vertebral fractures, ( 66–76 ) 17 hip fractures, ( 74–90 ) and 10 other fracture sites such as humerus or wrist. ( 75,76,90–97 ) Nineteen studies developed CNN models for image analysis.…”
Section: Resultsmentioning
confidence: 99%
“…( 66,67,71,72,77–86,90,91,93–95 ) Others used features extracted from images or collected from non‐imaging data. ( 68–70,73–77,87–89,92,96,97 ) Studies reported average best AUC of 0.92 (range 0.63 to 1.00) and average best accuracy of 89.8% (range 78.4% to 99.1%]. Surprising findings were that hospital‐related variables, such as the scanner device model, were better predictors of fractures than patients' characteristics or their images (AUC = 0.89 [95% confidence interval (CI) 0.87–0.91] versus 0.79 [95% CI 0.75–0.82] and 0.78 [95% CI 0.74–0.81], respectively), ( 77 ) which the authors acknowledged as a potential bias induced by the triage process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zolhavarieha and Parry (2017) developed a candidate matrix from their developed CDSS framework called Knowledge Quality Assessment (KQA) for discovering and evaluating the clinical knowledge for CDSS design. Chen et al (2018) investigated an association of inhaled corticosteroids and fracture in order to develop a CDSS. In the research Chen et al (2018) particularly addressed the issue of improving predictive performance of the CDSS.…”
Section: Cdss Researchmentioning
confidence: 99%
“…Chen et al (2018) investigated an association of inhaled corticosteroids and fracture in order to develop a CDSS. In the research Chen et al (2018) particularly addressed the issue of improving predictive performance of the CDSS. Yu (2015) improved the utility of the CDSS by focusing on the importance of the relationship of knowledge bases and the CDSS system as key drivers of rapid learning in clinical care service.…”
Section: Cdss Researchmentioning
confidence: 99%